Internal Versus External Labour Flexibility: A Two-Plant Comparison in Canadian Manufacturing - Grenier, Jean-Noël; Giles, Anthony; Bélanger, Jacques (Relations industrielles / Industrial Relations, 1997)
This article examines the divergent patterns of labour flexibility in two Canadian power transformer plants owned by the same company and producing similar products with identical technologies. The case study results are used to point to three oversimplifications in the flexibility debate: the claim that "numerical" and "functional" flexibility are incompatible; the argument that North American management relies more heavily on external flexibility than on internal flexibility; and the widespread contention that the traditional collective agreement is the chief barrier to achieving a more flexible organization of production in North America.